The International Conference on ASEAN 2019 2019
DOI: 10.1515/9783110678666-028
|View full text |Cite
|
Sign up to set email alerts
|

Malaysia- Indonesia Soft Power and Foreign Policy: Strengthening Bilateral Relations Through Internationalization of Higher Education

Abstract: There is continuity and change in Malaysia's foreign policy in the past six decades under the leadership of six Prime Ministers. The 'returns' of Mahathir as the 7 th Prime Minister of Malaysia might probably signal the changes in the contemporary Malaysia's foreign policy in responds to the globalization. One of the important sectors that actively embrace the positivity of globalization is higher education. There are a positive capability of higher education institutions (HEIs) as an instrument of Soft Power … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Joseph Nye has suggested that universities can play crucial role in foreign policy discussion and better awareness about power and its projections, compared to coercive diplomacy and hard power. Globalisation and the emergence of ‘knowledge-based society and economy’ have spurred the higher educational institutions (HEIs) to deal with increasing demands and expectations beyond borders and their transnational dimensions (Abd Wahab & Harza, 2021). Thus transnationalisation in content and internationalisation in expanse have become integral and vital characters of education reforms and practices in this part of Asia, mainly Malaysia and Singapore.…”
Section: The Soft Power Of Education: Our Contemporary Experiencesmentioning
confidence: 99%
“…Joseph Nye has suggested that universities can play crucial role in foreign policy discussion and better awareness about power and its projections, compared to coercive diplomacy and hard power. Globalisation and the emergence of ‘knowledge-based society and economy’ have spurred the higher educational institutions (HEIs) to deal with increasing demands and expectations beyond borders and their transnational dimensions (Abd Wahab & Harza, 2021). Thus transnationalisation in content and internationalisation in expanse have become integral and vital characters of education reforms and practices in this part of Asia, mainly Malaysia and Singapore.…”
Section: The Soft Power Of Education: Our Contemporary Experiencesmentioning
confidence: 99%